Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Multirasa Nusantara ( Yoshinoya Restaurant ) Bekasi: The Effect of Work Motivation and Work Discipline on Employee Performance at PT Multirasa Nusantara (Yoshinoya Restaurant) Bekasi - Biyantomo, Hendro Poer; Indriyani, Furi (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Employee performance plays a crucial role in determining organizational success, particularly in the fast-food service industry, which demands speed, accuracy, and consistent service quality. PT Multirasa Nusantara (Yoshinoya Restaurant) Bekasi experiences issues related to employee discipline, such as tardiness, unexcused absences, and inconsistent compliance with work procedures, which may negatively affect employee performance. Therefore, this study aims to analyze the effect of work motivation and work discipline on employee performance at PT Multirasa Nusantara (Yoshinoya Restaurant) Bekasi. This research employed a quantitative approach using a survey method. The population consisted of 40 employees, all of whom were selected as the research sample through a saturated sampling technique. Data were collected through Likert-scale questionnaires, observation, and documentation. Data analysis was conducted using SPSS software, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results show that work motivation has a positive and significant effect on employee performance, and work discipline also has a positive and significant effect on employee performance. Furthermore, work motivation and work discipline simultaneously have a positive and significant influence on employee performance. These findings indicate that enhancing employee motivation and strengthening work discipline are essential strategies for improving employee performance in a fast-food service environment.